Bengali society, culture and Bengali Advertisements. (বাঙালি সমাজ, সংস্কৃতি ও বাংলা বিজ্ঞাপন) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
The questions of who the Bengalis are or whether they have a specific cultural identity, remains unsolved. Nevertheless, various theorists, essayists, writers have tried to find a central characteristic of Bengali in various context. Although almost none of them could finally pin down ‘Bengali’ in any specific definition, Bengalis have carried some symbols for a long time and also have broken many of them. The new Bengalis have emerged from that constant process of creation and recreation. Bengalis have always shined through their endless conversations (adda), attire, love of literature, travelling, festivals (mainly durga puja), food habits. Kolkata, the city of joy, was the centre. Apart from these, many Bengalis have shone with their own light in different parts of the world. Across geographical, political., social, linguistic distance, they remain absolutely ‘Bengali’ till death. Yet, the above traits are the hallmarks of the average Bengali, which he carries from generation to generation in his life. Advertising generally believes in the practice of popularity. This article will try to see how the cultural, political, social and emotional symbols, cherished by Bengalis, have diversified the Bengali Advertisements. The advertisements have masterfully portrayed these symbols in the copies and images. The economic condition of the country deeply affects the society. The last decade of the 20th century was perhaps the most important economic period in post-independent India. As the doors of world capital were opened to India, some significant changes took place in people’s mind. Bengali’s cultural symbols have rapidly changed due to the strong influence of new economy. The centuries-old, acquired characteristics of Bengalis have changed. The advertisement clearly captures the changing image of that ‘Bengali’ being.  This article will try to understand this particular subject using various examples of advertisements. The period chosen for the discussion is the period from the Second World War (1939) to the beginning of the twenty first century.
Keywords: Bengali Advertisements; Characteristics; Economy; Symbol; Popular; Diversity